Kearifan Lokal Desa Kuncen Mempertahankan Budaya Menjemur Krupuk Diatas Makam Berbasis Market Place - Sita, anisfebriana (LP2M IAIN Sultan Amai Gorontalo, 2022)
The local wisdom is the activation of artistic potential that has been passed down through generations and developed from indigenous culture. This study aimed to describe Kuncen Village's indigenous wisdom in preserving the tradition of drying crackers on graves based on Market Place. The researcher conducted this study in Kuncen Village, Padangan District, Bojonegoro Regency, East Java Province. The subjects of this study were the Entrepreneurs in Kuncen Village. The data collecting strategy was observation using cell phones to record and interview sources. The findings indicated that the people retained graves (Pesarean) due to a shortage of land for drying crackers. Furthermore, this effort aimed to preserve Kuncen Village's indigenous wisdom and guarantee the continuation of cracker market-based sales.